Students awareness of Shariah hotel influence behavioral intention to stay at Shariah - Zakaria, Norhafizah; Yahud, Noriana; Abu Hassan, Nur Afiqah; Apo, Patricia Olivia (2015)
Tourism is a sector that has been recognized by the Malaysia government as an economic catalyst for the country. It has been significant growth in the hotel industry such as Malaysia, for instance, has been leading the way in the halal tourism industry and had been successful in trying to attract Muslim tourist from all over the world. The paper briefly discussed issues which focus in Shariah Compliance Hotel in Malaysia. It attempt to examine the relationship of service quality, hotel's facilities an brand image of the hotel towards the behavioral intention to stay at Shariah Compliance Hotel. Apart from that, this study also highlights the students of Shariah Compliance Hotel practices in Malaysia such as Perdana Hotel in Kota Bharu. In this study, a questionnaires was written in Malay and English. This questionnaires was distributed to the respondent at the Pengkalan Chepa campus, University Malaysia Kelantan. This questionnaires was used as the instruments to gather the information for this research. In this study, the respondents was choose from the 3487 students in Pengkalan Chepa campus, University Malaysia of Kelantan which narrowed down into 346 of students. Data collection to find out about this study was used descriptive and correlation research under non - experimental research. This research also uses quantitative research which is used the program that is use to analysis the data is called Statistical Program for Social Science (SPSS) version 22. As a conclusion, it can be summarized that all independents variables are the important to influence behavioral intention to stay at Shariah Compliance Hotel. The result showed that the hotel's facilities is the most important influences the behavioral intention to stay at Shariah Compliance Hotel, followed by the service quality and lastly brand images.